2022
DOI: 10.1038/s41380-022-01708-2
|View full text |Cite
|
Sign up to set email alerts
|

Advancing preclinical models of psychiatric disorders with human brain organoid cultures

Abstract: Psychiatric disorders are often distinguished from neurological disorders in that the former do not have characteristic lesions or findings from cerebrospinal fluid, electroencephalograms (EEGs), or brain imaging, and furthermore do not have commonly recognized convergent mechanisms. Psychiatric disorders commonly involve clinical diagnosis of phenotypic behavioral disturbances of mood and psychosis, often with a poorly understood contribution of environmental factors. As such, psychiatric disease has been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 206 publications
(227 reference statements)
0
7
0
Order By: Relevance
“…While animal models are informative, translating these findings directly to humans can be uncertain. Additionally, hiPSC models, despite their sophistication, may not fully capture the intricacies of human brain development in vivo ( Dixon and Muotri, 2023 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…While animal models are informative, translating these findings directly to humans can be uncertain. Additionally, hiPSC models, despite their sophistication, may not fully capture the intricacies of human brain development in vivo ( Dixon and Muotri, 2023 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…One exciting application for the use of neural organoid systems is the study of a wide-range of human neurological diseases using human in vitro models 52,53 , which critically depends on the in vivo fidelity of cell-types produced in organoids. Neural organoids have been used to model and investigate human disorders of neurodevelopmental 3,54 , neuropsychiatric [55][56][57] , and neurodegenerative [58][59][60] nature, as well as infectious diseases 28,61,62 . It is essential that organoid systems model in vivo cell-types with extreme fidelity to fully realize the therapeutic potential of human organoids and ensure findings in these in vitro models are not specific to potential artifactual or inaccurate in vitro biology.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have utilized patient-derived iPSCs to create both 2D neuronal cultures and 3D brain organoids in order to elucidate the mechanistic basis of BD pathogenesis. Some of the most significant pathophysiological mechanisms identified thus far include ion channel dysfunction [ 25 , 26 ], impaired calcium signalling [ 27 , 28 ], mitochondrial dysfunction [ 29 , 30 ], inflammation [ 31 ], and neuronal hyperexcitability [ 32 , 33 ]. A recent study demonstrated that iPSC-derived cortical spheroids from BD patients exhibit smaller sizes, a lower proportion of neurons, and reduced neural network activity in comparison to control spheroids [ 34 ].…”
Section: Introductionmentioning
confidence: 99%